Dynamic Shape Transformation of a DNA Scaffold Applied for an Enzyme Nanocarrier - Lin, Peng; Dinh, Huyen; Nakata, Eiji; Morii, Takashi (Frontiers in Chemistry, 2021)
Structural programmability and accurate addressability of DNA nanostructures are ideal characteristics for the platform of arranging enzymes with the nanoscale precision. In this study, a three-dimensional DNA scaffold was designed to enable a dynamic shape transition from an open plate-like structure to its closed state of a hexagonal prism structure. The two domains in the open state were folded together to transform to the closed state by hybridization of complementary short DNA closing keys at both of the facing edges in over 90% yield. The shape transformation of DNA scaffold was extensively studied by means of the fluorescence energy transfer measurement, atomic force microscope images and agarose gel electrophoretic analyses. A dimeric enzyme xylitol dehydrogenase was assembled on the DNA scaffold in its open state in a high loading yield. The enzyme loaded on scaffold was subsequently transformed to its closed state by the addition of short DNA closing keys. The enzyme encapsulated in the closed state displayed comparable activity to that in the open state, ensuring that the catalytic activity of enzyme was well maintained in the DNA nanocarrier. The nanocarrier with an efficient encapsulation ability is potentially applicable for drug delivery, biosensing, biocatalytic and diagnostic tools.